Клиническое применение термографического метода контроля температуры сердца - Шликов, Владислав Валентинович; Данилова, Валентина Анатольевна (НТУ "ХПИ", 2017)
Предложен метод термографического контроля температуры на поверхности миокарда при операциях на открытом сердце, основанный на вычислении плотности теплового потока через поверхность миокарда по данным градиентов температур, которые определяются из термографических изображений сердца при гипотермии и гипертермии в условиях искусственного кровообращения. Применение разработанной математической модели теплообмена для поверхностного слоя миокарда позволяет определить границы между прогретыми и охлажденными участками миокарда при проведении гипотермии или гипертермии сердца.

A method is proposed for thermographic temperature monitoring on the surface of the myocardium during open heart operations based on calculating the heat flux density through the surface of the myocardium from temperature gradient data, which are determined from thermal images of the heart under hypothermia and hyperthermia under conditions of artificial circulation. Application of the developed mathematical model of heat exchange for the surface layer of the myocardium allows us to determine the boundaries between heated and cooled portions of the myocardium during hypothermia or cardiac hyperthermia. Evaluation of the rate of heat spread in the myocardium, which is performed for the time intervals for which the heart is cooled or warmed, indirectly makes it possible to assess the state of small coronary vessels in the myocardium.
Clinical application of the thermographic method of monitoring heart temperature
Keywords: сосуды; тепловой поток; распределение температуры; миокард; искусственное кровообращение; гипотермия; гипертермия; градиент; термограмма сердца; blood vessels; heat flow; temperature distribution; myocardium; artificial circulation